(untitled) (Annals of Medical Research, 2021)
Aim: Patients who performed wedge resection of the lesser curvature of the stomach due to GIST were evaluated for delayed gastric emptying.Material and Methods: Thirty patients who underwent wedge gastric resection for GIST in stomach between 2009-2019 were evaluated retrospectively. In Seven patients it is located in lesser curvature. Results: Fifty-five patients were operated between 2009 and 2019 for GIST.In 7 patients, GIST was found to be located in the lesser curvature of the stomach. Of the 7 patients, 2 (%28) were male and 5 (%72) were female. Laparoscopy was performed in 4 patients and conventional procedure was performed in 3 patients. The average age was 56±10.5 (46-67) years in the conventional procedure group, and 61.5±10.4 (50-73) in the laparoscopic group. Average hospital stay was 4.67±1.5 (3-6) days for conventional procedure and, 2.75±0.9 (2-4) days for the laparoscopic group. Age and length of hospital stay were not different between the two groups (p=0.522 and p=0.094, respectively).All patients had normal radiological findings. Stool discharge was observed on postoperative day 3 at the latest.Conclusion: In conclusion, resection of lesser curvature (with laparoscopic or conventional procedure) GISTs with a tumor free surgical margin staying near to the gastric wall to prevent vagal nerve injury is feasible without gastric emptying problems.